THE ROLE OF THE NOW CORPUS IN DEVELOPING STUDENTS’ LANGUAGE SKILLS - Barnoyeva Nilufar Yoqubovna (Bright Mind Publishing, 2025)
This study explores the role of the NOW (News on the Web) Corpus in enhancing students’ language skills, focusing on vocabulary acquisition, collocation awareness, and contextual usage. The research examines how Corpus Linguistics facilitates language learning by providing authentic, up-to-date language data. Using both qualitative and quantitative methods, the study evaluates students’ performance before and after integrating the NOW Corpus into their learning process. Results indicate a significant improvement in students’ ability to recognize and use collocations, understand lexical nuances, and develop more natural language production. The discussion highlights the teaching implications of using corpus-based learning and the challenges associated with its integration into the curriculum.
Keywords: NOW Corpus, Corpus Linguistics, language skills, vocabulary acquisition, collocation awareness, contextual learning, language learning.